Metal chelate, preparation method thereof and application of metal chelate in preparation of light conversion material
By developing a metal chelate for light conversion materials, the problem of insufficient UV bleaching resistance and compatibility of existing light conversion materials is solved, and efficient UV light conversion and stable photoelectric conversion efficiency are achieved. in silicon crystal photovoltaic cells and other photovoltaic devices.
Patent Information
- Application Number
- CN202411629465.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing photoconverting materials have shortcomings in their UV bleaching resistance and compatibility, which has limited their application in silicon crystal photovoltaic cells and cannot effectively protect the cells from UV erosion.
Develop a metal chelate with the chemical formula of MLxAyBz, where M is the main group, transition or rare earth metal ions, L is a rigid chelating agent with more than 2 electron-donating functional groups, and A is a phosphine oxide containing fat or aromatic substituents Compound, B is an alkyl cationic surfactant, and a photoconversion material with high-efficiency light conversion performance and excellent UV bleaching resistance is prepared through a reaction between 50 and 110°C.
The metal chelate material exhibits strong light absorption ability in the ultraviolet region, efficiently converts ultraviolet light into visible light, with a quantum efficiency of 80~100%, and has good compatibility with common polymer materials, significantly improving silicon crystals The photoelectric conversion efficiency of photovoltaic cells and exhibits stable light absorption and emission performance after ultraviolet irradiation.
Smart Images

Figure CN119143790A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a photoconversion material, and in particular to a metal chelate, a preparation method and application thereof, such as application in the preparation of a photoconversion material. Background Art
[0002] With the growing global demand for renewable energy, the photovoltaic industry has ushered in an opportunity for rapid development. Silicon photovoltaic technology has become the mainstream choice for green and sustainable energy with its mature production process and high photoelectric conversion efficiency. However, when photovoltaic modules are operated outdoors for a long time, they will inevitably be corroded by ultraviolet rays, which will not only accelerate the aging of the materials, but also lead to a significant decrease in power generation efficiency. Taking HJT cells as an example, it has the advantages of high photoelectric conversion efficiency, good weak light performance, low temperature coefficient, simple process flow and low environmental pollution, and has become the mainstream direction of the development of the next generation of silicon photovoltaics. Compared with other types of silicon photovoltaic cells, HJT cells are more susceptible to ultraviolet erosion. Once the Si-H bonds on its surface are destroyed by ultraviolet rays, the performance of the cell will drop sharply. The current solution to the problem of ultraviolet sensitivity of silicon photovoltaic cells is to add ultraviolet absorbing materials to the encapsulation film to cut off ultraviolet rays before the light reaches the silicon material. This method can effectively protect silicon photovoltaic cells from ultraviolet erosion, but at the same time, the electrical energy brought by ultraviolet rays will also be lost.
[0003] Photoconversion materials provide an innovative solution to this problem. This type of material can convert harmful and inefficiently used ultraviolet light into efficiently used visible light. That is, while effectively blocking ultraviolet rays, it improves the utilization rate of sunlight in silicon photovoltaics and achieves higher photoelectric conversion efficiency. In addition, the application of photoconversion materials breaks through the constraints of the efficiency limit of the Shockley-Queisser theory. It is no longer limited to improving efficiency by reducing energy losses, but by enhancing the utilization rate of sunlight, further improving the photoelectric conversion efficiency above the existing theoretical limit, bringing a new idea of efficiency improvement and cost reduction to the photovoltaic industry.
[0004] Some researchers have proposed an organic (polymer or oligomer) photoconversion material that exhibits a high luminescence quantum efficiency (close to 100%), and the corresponding photoconversion film can significantly improve the photoelectric conversion efficiency of silicon photovoltaic cells. However, this material is not resistant to ultraviolet bleaching and is prone to degradation under ultraviolet irradiation of standard sunlight intensity, resulting in a decrease in its ultraviolet absorption and photoconversion performance. Its service life is much shorter than that of silicon photovoltaic cells, which will limit its application in silicon photovoltaics. Other researchers have proposed a rare earth organic ligand nano / micron down-conversion material, which also has the problem of poor resistance to ultraviolet bleaching. In order to improve the antioxidant capacity of this type of material, some researchers have used PMMA microspheres to encapsulate rare earth organic ligand nano / micron down-conversion materials. This operation can improve the stability of the material to a certain extent, but it cannot fundamentally solve the problem of poor resistance to ultraviolet bleaching of the material itself. In addition, the rare earth organic ligand itself is already nano / micron scale, which is easy to scatter visible light, thereby reducing the utilization rate of light. In addition, some researchers have proposed a quantum dot-doped silica colloid. The biggest problem with this light-conversion material is that the absorption wavelength is short and the absorption range cannot cover the UVA region, which cannot effectively protect silicon photovoltaic cells. Therefore, the development of light-conversion materials with both excellent light-conversion performance and excellent anti-ultraviolet bleaching performance is still an important challenge to be overcome.
[0005] In addition, the compatibility of light conversion materials with packaging film materials is another key factor that determines whether they can be applied to light conversion films. Due to the lag in the development of light conversion materials, most reports currently focus on the optimization of cutoff materials and related additives in packaging films. Therefore, the development of new light conversion materials must take into account their compatibility with packaging film materials, which has long been a difficult problem in this field. Summary of the invention
[0006] The main purpose of the present application is to provide a metal chelate, a preparation method thereof and an application in the preparation of a light conversion material, so as to overcome the deficiencies in the prior art.
[0007] In order to achieve the above-mentioned invention object, the technical solution adopted in this application includes: The first aspect of the present application provides a metal chelate compound, the chemical formula of which is ML x A y B z, wherein M is at least selected from a family metal ion, a transition metal ion or a rare earth metal ion, L is selected from a rigid chelating agent having two or more electron-donating functional groups, A is selected from a phosphine oxide compound containing 1 to 3 aliphatic substituents or aromatic substituents, B is selected from an alkyl cationic surfactant, x=2 to 4, (y+z)=0 to 4, x is an integer, y and z are both greater than or equal to 0, and y and z are not 0 at the same time.
[0008] The second aspect of the present application provides a method for preparing a metal chelate, comprising: reacting a mixture containing MX3, L, A, B and an anhydrous polar solvent at 50-110° C. to obtain a light conversion material ML x A y B z ; Wherein, M is a trivalent metal ion and is at least selected from a family metal ion, a transition metal ion or a rare earth metal ion, X is selected from a halogen ion, L is selected from a rigid chelating agent having more than two electron-donating functional groups, A is selected from a phosphine oxide compound containing 1 to 3 aliphatic substituents or aromatic substituents, B is selected from an alkyl cationic surfactant, x=2 to 4, (y+z)=0 to 4, x is an integer, y and z are both greater than or equal to 0, and y and z are not 0 at the same time.
[0009] The third aspect of the present application provides the use of the metal chelate in preparing a light conversion material, a photovoltaic device, an anti-counterfeiting structure or a light-emitting structure, etc. The light conversion material can convert the absorbed light of a first wavelength into light of a second wavelength, which is greater than the first wavelength.
[0010] Compared with the prior art, the metal chelate provided in this application can be applied as a new type of photoconversion material, and exhibits strong light absorption ability in the ultraviolet region, and can efficiently convert ultraviolet light into long-wavelength visible light, etc., and the quantum efficiency of photoconversion is 80~100%. Moreover, the photoconversion material not only has excellent photoconversion performance and a suitable light absorption range, but also has excellent anti-ultraviolet bleaching performance. At the same time, the photoconversion material has excellent compatibility with polymer materials such as EVA (ethylene-vinyl acetate copolymer), PVB (polyvinyl butyral ester), POE (polyolefin elastomer), and EPE (polyethylene foam). The photoconversion film based on the photoconversion material can significantly improve the photoelectric conversion efficiency of photovoltaic devices such as silicon crystal photovoltaic cells. In addition, the photoconversion material can also be used to prepare anti-counterfeiting materials, decorative lighting structures, etc., and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] The exemplary embodiments of the present application are described below with reference to the accompanying drawings. It should be understood that these specific descriptions are only used to teach those skilled in the art how to implement the present application, and are not intended to exhaust all feasible methods of the present application, nor to limit the scope of protection of the present application.
[0012] Figure 1 is the infrared spectrum of the metal chelate LCA2 in Example 2; Figure 2 This is a thermal stability test diagram of a metal chelate LCA2 provided in Example 2; Figure 3 This is a test chart of the anti-ultraviolet bleaching property of a light conversion film based on the metal chelate LCA2 in Example 2; Figure 4 is a JV curve diagram of a silicon crystalline photovoltaic cell encapsulated by a cut-off film, a light conversion film and a high-transmittance film in Example 2; Figure 5 is the transmittance curve of the light conversion film and the high transmittance film in Example 2; Figure 6 It is the pattern of the squirrel under natural light and ultraviolet light in Example 2; Figure 7 is a photograph of the polymer profile under the irradiation of natural light and ultraviolet light waveguide in Example 2; Figure 8 is the infrared spectrum of the metal chelate LCA3 in Example 3; Fig. 9 This is a thermal stability test graph of a metal chelate LCA3 provided in Example 3; Fig.10 is a JV curve diagram of a silicon crystalline photovoltaic cell encapsulated by a cut-off film, a light conversion film and a high-transmittance film in Example 3; Fig.11 3 is the transmittance curve of the light conversion film and the high transmittance film in Example 3. DETAILED DESCRIPTION
[0013] As mentioned above, in view of the many defects of existing photoconversion materials, the applicant has proposed the technical solution of the present application after long-term research and practice, thereby well overcoming the shortcomings of the prior art. In summary, the present application provides a metal chelate with excellent thermal stability, resistance to ultraviolet light bleaching and polymer compatibility, which can efficiently convert harmful and inefficiently utilized ultraviolet rays into visible light that can be used by photovoltaic devices, etc., so it can be used as a photoconversion material in photovoltaic, anti-counterfeiting, decorative lighting and other fields. The technical solution of the present application will be described in detail below.
[0014] Some embodiments of the present application provide a metal chelate compound with the chemical formula ML x A y B z, wherein M is at least selected from a family metal ion, a transition metal ion or a rare earth metal ion, L is selected from a rigid chelating agent having more than two electron-donating functional groups, A is selected from a phosphine oxide compound containing 1 to 3 aliphatic substituents or aromatic substituents, B is selected from an alkyl cationic surfactant, x=2 to 4, (y+z)=0 to 4, x is an integer, y and z are both greater than or equal to 0, and y and z are not 0 at the same time. Preferably, y is greater than 0. Preferably, y and z are both greater than 0, so that the metal chelate has better luminescent properties and better compatibility with the polymer.
[0015] In one embodiment, M is selected from trivalent metal ions such as Al 3+ , Ga 3+ 、In 3+ 、Mo 3+ 、Eu 3+ Sc 3+ , Gd 3+ or Y 3+ These ions have high valence and strong coordination ability, which can make the metal chelate have good luminescent properties.
[0016] In one embodiment, L may include one or more of hydroxyquinoline derivatives, hydroxynaphthyridine derivatives, b-diketone derivatives or o-phenanthroline derivatives, and is not limited thereto. For example, L may be selected from, but not limited to, one or more combinations of the following compounds: ; Among them, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 They are independently selected from hydrogen or aliphatic substituents or aromatic substituents containing 1 to 20 carbon atoms, for example, the aliphatic substituents may be methyl, ethyl, propyl, butyl, hexyl or octyl, etc., but are not limited thereto; the aromatic substituents may be phenyl, benzyl, thienyl or pyrrolyl, etc., but are not limited thereto. The distance between the two electron-donating functional groups of these complexes is more closely matched to the distance between each two orbitals of the coordinated metal.
[0017] In one embodiment, the carbon number of each aliphatic substituent or aromatic substituent in A is 1 to 20. Further, the aliphatic substituent in A includes a saturated alkyl group or a saturated alkoxy group, and the aromatic substituent includes an aromatic hydrocarbon group. Exemplarily, the saturated alkyl group includes a methyl group, an ethyl group, a propyl group, a butyl group, a hexyl group or an octyl group, etc., and is not limited thereto. The saturated alkoxy group includes a methoxy group, an ethoxy group, a propoxy group, a butoxy group, a hexyl group or an octyl group, etc., and is not limited thereto. The aromatic hydrocarbon group includes a phenyl group, a benzyl group, a thienyl group or a pyrrolyl group, etc., and is not limited thereto.
[0018] Furthermore, A in the metal chelate may be a single phosphine oxide compound or a combination of two or more phosphine oxide compounds.
[0019] In one embodiment, the hydrophilic group in the alkyl cationic surfactant includes an ammonium cation, and the hydrophobic group includes an alkyl group having a carbon number of 1 to 20. Exemplarily, the hydrophilic group includes trimethylammonium bromide ion, trimethylammonium chloride ion, triethylammonium bromide ion, triethylammonium chloride ion, pyridinium bromide ion or pyridinium chloride ion, etc., and is not limited thereto. The hydrophobic group includes dodecyl, tetradecyl or hexadecyl, etc., and is not limited thereto.
[0020] Furthermore, B in the metal chelate may be a single alkyl cationic surfactant or a combination of two or more alkyl cationic surfactants.
[0021] In one embodiment, x is preferably 3 or 4.
[0022] The metal chelate of the present application can absorb ultraviolet rays and convert them into long-wavelength light, especially into visible light, with a luminous quantum efficiency of 60-100%, preferably 80-100%. At the same time, the metal chelate has excellent thermal stability, and the thermal decomposition temperature is greater than 300 ° C. In addition, the metal chelate also has excellent resistance to ultraviolet bleaching. Accelerated aging experiments show that after 180 kWh of ultraviolet irradiation, its light absorption and emission performance attenuation is very small. In addition, the metal chelate has excellent compatibility with polymer materials such as EVA, PVB, POE and EPE.
[0023] Some embodiments of the present application provide a method for synthesizing a metal chelate, comprising: reacting a mixture containing MX3, L, A, B and an anhydrous polar solvent at 50-110° C. to obtain a light conversion material ML x A y B z ; Wherein, M is a trivalent metal ion and is at least selected from a family metal ion, a transition metal ion or a rare earth metal ion, X is selected from a halogen ion, L is selected from a rigid chelating agent having two or more functional groups, A is selected from a phosphine oxide compound containing 1 to 3 aliphatic substituents or aromatic substituents, B is selected from an alkyl cationic surfactant, x=2 to 4, (y+z)=0 to 4, x is an integer, y and z are both greater than or equal to 0, and y and z are not 0 at the same time.
[0024] In one embodiment, the usage ratio of MX3, L, A, and B is 1:1-4:0-4:0-4, preferably 1:2-4:0-4:0-4, and more preferably 1:3-4:0-4:0-4.
[0025] In one embodiment, the preparation method specifically comprises: reacting the mixture at 50-110° C. for 1-10 hours, then cooling to room temperature, and removing the solvent therein to obtain the metal chelate.
[0026] In one embodiment, X is at least selected from F - , Cl - or Br - .
[0027] In one embodiment, the anhydrous polar solvent includes one or more of methanol, ethanol, isopropanol, acetonitrile, DMF, THF, and dioxane, but is not limited thereto.
[0028] The metal chelate synthesis method provided in the present application is simple and easy to operate, has good controllability, high yield (>90%), low cost, and is suitable for large-scale production.
[0029] Some embodiments of the present application also provide the use of the metal chelate in preparing a light conversion material, wherein the light conversion material can convert the absorbed light of a first wavelength into light of a second wavelength, wherein the second wavelength is greater than the first wavelength. Furthermore, the light of the first wavelength includes ultraviolet light. The light of the second wavelength includes visible light.
[0030] Some embodiments of the present application also provide a down-conversion luminescent material, which includes the metal chelate. Further, the down-conversion luminescent material may also include other light conversion materials besides the metal chelate, such as fluorescent quantum dots, etc., but is not limited thereto.
[0031] Some embodiments of the present application also provide uses of the metal chelate or the down-conversion luminescent material in the preparation of products such as photovoltaic devices, anti-counterfeiting structures or luminescent structures.
[0032] Some embodiments of the present application provide an optical structure, including a base component and a light conversion agent dispersed in the base component, wherein the light conversion agent includes the metal chelate or the down-conversion luminescent material.
[0033] In one embodiment, the optical structure comprises 0.2 wt‰ to 5 wt‰ of a light conversion agent.
[0034] In one embodiment, the light conversion agent may further include one or more other light conversion materials besides the metal chelate, such as fluorescent quantum dots, etc., but is not limited thereto.
[0035] Furthermore, the photoconverter is uniformly dispersed in the base component.
[0036] In one embodiment, the base component includes a polymer. Exemplarily, the polymer includes one or more combinations of EVA, PVB, POE or EPE, but is not limited thereto.
[0037] In one embodiment, the optical structure is in a film shape, that is, the optical structure may be a light conversion film.
[0038] In one embodiment, the light transmittance of the optical structure is above 80%.
[0039] The optical structure provided by the present application, such as the light conversion film, has excellent photothermal stability, and can significantly improve the photoelectric conversion efficiency of photovoltaic devices such as silicon photovoltaic cells, and also has excellent anti-ultraviolet bleaching performance. After 180 kwh of UVA+UVB ultraviolet light, the absorption and luminescence performance decays to 0.01~5%. Among them, the changes in the attenuation of absorption and luminescence performance are corresponding, that is, their attenuation ratios are the same. Here, the percentage of absorbance reduction before and after illumination is used as the attenuation index DN. This index also corresponds to the degradation of the optical structure material.
[0040] Some embodiments of the present application also provide a method for preparing the optical structure, which comprises: At least a light conversion agent is mixed with a polymer, and then the resulting mixture is heated and melted at a set temperature to form an optical structure; Wherein, the photoconverter includes the metal chelate, and the mass ratio of the metal chelate to the polymer is 0.2‰ to 5‰, and the set temperature is above the glass transition temperature of the polymer.
[0041] In one embodiment, the preparation method specifically comprises: mixing the photoconverter or the solution of the photoconverter with polymer particles to obtain the mixture. The solvent in the solution is preferably a volatile low-polarity solvent, such as petroleum ether, ethyl acetate, toluene, etc.
[0042] In one embodiment, the preparation method specifically includes: heating and melting the mixture to form a film, thereby obtaining the optical structure. The film forming process used includes cast film forming, blow molding, etc.
[0043] In these embodiments, the compatibility of the photoconverter with the polymer is compared using the absorbance in the visible region (400-700 nm) before and after the photoconverter is added to the polymer film as a parameter. Specifically, the absorbance ratio at 600 nm is used as the compatibility index R600, which ranges from 0.995 to 1.005.
[0044] In some cases, the photoconverter may be dispersed in a polymer solution or a polymer monomer solution to prepare a precursor liquid, and then prepared into a film through processes such as spin coating, scraper coating, spray coating, and curing and cross-linking reactions, thereby obtaining the optical structure.
[0045] The method for preparing the optical structure provided in the present application is also very simple and easy to operate, and is compatible with the preparation process of conventional photovoltaic device encapsulation films, and can well meet the needs of industrial production.
[0046] Some embodiments of the present application further provide a photovoltaic device, including a photovoltaic cell and a packaging structure connected to the photovoltaic cell, wherein the packaging structure includes the optical structure.
[0047] Furthermore, the photovoltaic cell may be wholly or partially encapsulated in the encapsulation structure.
[0048] Furthermore, the optical structure may be a light conversion film in the packaging structure, but is not limited thereto.
[0049] Furthermore, the photovoltaic cell includes a silicon solar cell, a perovskite photovoltaic cell, an organic photovoltaic cell, a copper indium selenide photovoltaic cell, a gallium arsenide photovoltaic cell or a cadmium telluride photovoltaic cell, etc., but is not limited thereto.
[0050] Due to the adoption of the optical structure, the photovoltaic device exhibits advantages such as higher photoelectric conversion efficiency, more stable working performance, and longer service life.
[0051] Some embodiments of the present application further provide an anti-counterfeiting structure, comprising a substrate and an anti-counterfeiting material layer distributed on the surface of the substrate, wherein the anti-counterfeiting material layer comprises the metal chelate or the down-conversion luminescent material.
[0052] Since the metal chelate basically only absorbs ultraviolet light, it will not affect the visual effect, and can emit strong visible light under ultraviolet irradiation, which is easy to be distinguished by the human eye. Therefore, the metal chelate can be used as an anti-counterfeiting material.
[0053] Furthermore, the metal chelate or the light conversion agent containing the metal chelate can be coated on the surface of an object, or mixed with other pigments and coated on the surface, and different colors can be displayed by ultraviolet irradiation, thus achieving a good anti-counterfeiting effect.
[0054] Some embodiments of the present application further provide a light-emitting device, including a light source and a light conversion structure coordinated with the light source, wherein the light conversion structure includes the metal chelate, the down-conversion luminescent material or the optical structure.
[0055] Furthermore, the light conversion structure is mainly arranged in the light emitting direction of the light source, and is connected to the light source or arranged at a distance from the light source. The light conversion structure can be in the form of a film, a shell (such as a lampshade), etc., but is not limited thereto.
[0056] For example, the metal chelate or the light conversion agent containing the metal chelate can be added to colorless transparent plastic, which will not affect the light transmittance of the plastic article in the visible region. Under ultraviolet light, visible light can be emitted, thereby obtaining a beautiful decorative lighting effect.
[0057] The technical solution of the present application will be explained in more detail below in conjunction with several embodiments, but these specific descriptions are only used to teach those skilled in the art how to implement the present application, rather than to exhaust all feasible methods of the present application, nor to limit the scope of the present application. Unless otherwise specified, the various raw materials in the following examples and comparative examples can be obtained from commercial sources, etc., and the test methods and test equipment used are also commonly used in the art.
[0058] For example, the light conversion performance, quantum efficiency, and UV bleaching resistance of the following metal chelates were tested using UV-visible spectroscopy, fluorescence integrating sphere, and absorbance variation with UV light intensity.
[0059] The light absorption performance, luminescence performance and quantum efficiency of the following light conversion films were characterized by UV-vis spectroscopy, fluorescence spectrometer and integrating sphere, respectively.
[0060] The following UV bleaching resistance test and aging performance test of the light conversion film are both carried out in an aging test chamber.
[0061] The chemical formula of the metal chelate in the following examples is ML x A y B z , wherein M is a trivalent metal ion, L is a rigid chelating agent, A is a phosphine oxide compound, and B is an alkyl cationic surfactant.
[0062] Example 1 The synthesis method of a metal chelate LCA1 provided in this embodiment comprises the following steps: adding AlCl3 (100 mmol), 8-isopropyl 4-hydroxynaphthyridine (300 mmol), tri-n-butylphosphine oxide (200 mmol) and tetradecyltrimethylammonium bromide (200 mmol) into a 1000 mL flask, and using 300 mL of anhydrous ethanol as a solvent, and then reacting the obtained mixture at 100°C for 2 hours. Then, the temperature is cooled to room temperature, and the solvent is removed to obtain LCA1, in which x=3, y and z are both 2 in the chemical formula.
[0063] The stability of LCA1 was tested, and the results showed that its thermal decomposition temperature was higher than 300°C, indicating that it has high stability.
[0064] The chemical structural formula of 8-isopropyl 4-hydroxynaphthyridine is: .
[0065] LCA1 was directly added to commercially available EVA polymer particles in an amount of 1‰, stirred and blended for 1 hour, heated to 150°C, and cast on a casting machine to form a light conversion film M1. The fluorescence quantum efficiency of the light conversion film M1 was 90%. In the UV aging box test, under a 180 W UV lamp, the attenuation index DN of the light conversion film M1 was 3% after continuous irradiation for 1000 hours, which showed good stability.
[0066] The light conversion film M1 is applied to a commercially available silicon photovoltaic cell using a vacuum laminator. The gas between the light conversion film and the cell surface is removed by vacuuming. The lamination temperature is controlled at 150°C. The compatibility index R600 between LCA1 and EVA as a light conversion agent in the light conversion film M1 is 0.998. Compared with the EVA high-transmittance film of the same thickness, the light conversion film M1 increases the power of the silicon photovoltaic cell by 0.3%; compared with the EVA high-cutoff film (film with added ultraviolet absorption material) of the same thickness, the power of the silicon photovoltaic cell increases by 1%.
[0067] Comparative Example 1 The synthesis method of a metal chelate LCA1a provided in this comparative example is basically the same as that in Example 1, except that tri-n-butylphosphine oxide is not added.
[0068] The performance of LCA1a and the light conversion film based on LCA1a were tested in the same manner as in Example 1. The results showed that the fluorescence quantum efficiency of the light conversion film based on LCA1a was about 15% lower than that of the light conversion film based on LCA1. The compatibility index R600 of LCA1a and EVA was about 0.321.
[0069] Comparative Example 2 The synthesis method of a metal chelate LCA1b provided in this comparative example is basically the same as that in Example 1, except that tetradecyltrimethylammonium bromide is not added.
[0070] The performance of LCA1b and the light conversion film based on LCA1b were tested in the same manner as in Example 1. The results showed that the fluorescence quantum efficiency of the light conversion film based on LCA1b was about 20% lower than that of the light conversion film based on LCA1. The compatibility index R600 of LCA1b and EVA was about 0.375.
[0071] Example 2 The present embodiment provides a method for synthesizing a metal chelate LCA2, comprising the following steps: adding titanium trichloride (100 mmol), 8-methyl 3-cyano 4-hydroxynaphthyridine (400 mmol), trioctylphosphine oxide (300 mmol) and dodecyltrimethylammonium bromide (100 mmol) into a 1000 mL flask, and using 300 mL acetonitrile as a solvent, and then reacting the formed mixture at 95° C. for 4 hours, then cooling to room temperature, and removing the solvent by evaporation to obtain LCA2, in which the chemical formula is x=4, y=3, and z=1.
[0072] The chemical structural formula of 8-methyl 3-cyano 4-hydroxynaphthyridine is: .
[0073] LCA2 was directly added to the EVA polymer particles at a dosage of 1‰, stirred and blended for 1 hour, and then the mixture was heated to 150°C and made into a light conversion film M2 using an upper casting machine, and its fluorescent quantum efficiency was increased to 92%.
[0074] In order to evaluate the stability of the light conversion film M2, it was placed in a UV aging box and continuously irradiated under a 180-watt UV lamp for 1,000 hours. The test results showed that the attenuation index DN of the light conversion film M2 was 2%, showing excellent light stability.
[0075] Finally, the light conversion film M2 was applied to the silicon photovoltaic cell using a vacuum laminator, and the gas between the light conversion film and the cell surface was removed by vacuuming, and the lamination temperature was controlled at 150°C. The compatibility index R600 of LCA2 and EVA in the light conversion film M2 was 0.999. Compared with the high-transmittance film of the same thickness, the power of the silicon photovoltaic cell with the light conversion film M2 increased by 0.4%; compared with the high-cutoff film of the same thickness, the power of the silicon photovoltaic cell with the light conversion film M2 increased by 1.2%.
[0076] Example 3 The synthesis method of a metal chelate LCA3 provided in this embodiment comprises the following steps: adding europium trichloride (1 mmol), 4-hydroxynaphthyridine (4 mmol), trimethylphosphine oxide (1 mmol) and hexadecyltrimethylammonium bromide (1 mmol) into a 1000 mL flask, and using 300 mL DMF as a solvent, and then reacting the resulting mixture at 110°C for 1.5 hours, then cooling to room temperature, and removing the solvent by evaporation to obtain LCA3, wherein x=4, y=1, and z=1 in the chemical formula. The infrared spectrum of LCA3 is as follows Figure 1 shown. Figure 2 The thermal stability test results of LCA3 are shown.
[0077] The chemical structural formula of 4-hydroxynaphthyridine is: .
[0078] LCA3 was directly added to the EVA polymer particles at a dosage of 1‰, and after 1 hour of stirring and blending, the mixture was heated to 150°C and made into a light conversion film M3 using an upper casting machine, and its fluorescent quantum efficiency was 88%.
[0079] In order to evaluate the stability of the light conversion film M3, it was placed in a UV aging box and continuously irradiated under a 180-watt UV lamp for 1,000 hours. The test results showed that the attenuation index DN of the light conversion film M2 was 3%, showing excellent light stability.
[0080] Finally, the light conversion film M3 is applied to the silicon photovoltaic cell using a vacuum laminator, and the gas between the light conversion film and the cell surface is removed by vacuuming, and the lamination temperature is controlled at 150°C. The compatibility index R600 of LCA3 and EVA in the light conversion film M3 is 1.001. Figure 3 Compared with the EVA high-transmittance film of the same thickness, the power of the silicon photovoltaic cell using the light conversion film M3 increased by 0.45%; compared with the EVA high-cutoff film of the same thickness, the power increased by 1.4%. The transmittance curves of the light conversion film M3 and the corresponding high-transmittance film are shown in Figure 2. Figure 4 shown.
[0081] Example 4 The synthesis method of a metal chelate LCA4 provided in this embodiment comprises the following steps: adding gadolinium trichloride (100 mmol), 4-methyl 8-hydroxyquinoline (400 mmol), trimethylphosphine oxide (200 mmol) and dodecylpyridinium bromide (100 mmol) into a 1000 mL flask, and using 300 mL of acetonitrile as a solvent. Then the formed mixture is reacted at 80° C. for 3 hours. Afterwards, it is cooled to room temperature, and the solvent is removed by evaporation to obtain LCA4, in which x=4, y=2, and z=1 in the chemical formula.
[0082] The structural formula of 4-methyl 8-hydroxyquinoline is as follows: .
[0083] LCA4 was directly added to the PVB polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 160°C. A light conversion film M4 was made using an upper casting machine, and its fluorescent quantum efficiency was 80%.
[0084] The UV aging box test shows that after continuous irradiation for 1000 hours under a 180-watt UV lamp, the attenuation index DN of the light conversion film M4 is 2%, showing excellent light stability. The light conversion film M4 is applied to the silicon crystalline photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 160°C. The compatibility index R600 of LCA4 and PVB in the light conversion film M4 is 0.997. Compared with the PVB high-transmittance film of the same thickness, the power of the silicon crystalline photovoltaic cell using the light conversion film M4 increased by 0.5%; compared with the PVB high-cutoff film of the same thickness, the power increased by 1.5%.
[0085] Example 5 The synthesis method of a metal chelate LCA5 provided in this embodiment comprises the following steps: adding europium trichloride (100 mmol), 4-methyl 7-cyano 8-hydroxyquinoline (300 mmol), trimethylphosphine oxide (100 mmol) into a 1000 mL flask, and using 300 mL DMF as a solvent. Then the resulting mixture is reacted at 70°C for 1 hour. Afterwards, it is cooled to room temperature, and the solvent is removed by evaporation to obtain LCA5, in which the chemical formula is x=3, y=1, and z=0. The infrared spectrum of the LCA5 is as follows: Figure 5 shown.
[0086] The structural formula of 4-methyl 7-cyano 8-hydroxyquinoline is as follows: .
[0087] The stability of LCA5 was tested and the results were as follows: Figure 6 As shown, its thermal decomposition temperature is higher than 300°C, and it has high stability.
[0088] LCA5 was directly added to the EPE polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 120°C. The light conversion film M5 was made using an upper casting machine, and its fluorescent quantum efficiency was 70%.
[0089] The UV aging box test shows that after continuous irradiation under 180W UV lamp for 1000 hours, the attenuation index DN of the light conversion film M5 is 2.5%. Figure 7 As shown, it shows good light stability. The light conversion film M5 is applied to the silicon photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 120°C. The compatibility index R600 of LCA5 and EPE in the light conversion film M5 is 1.001. Figure 8 As shown, compared with the EPE high-transmittance film of the same thickness, the power of the silicon photovoltaic cell using the light conversion film M5 increased by 0.4%; compared with the EPE high-cutoff film of the same thickness, the power increased by 1.3%. In addition, Fig. 9 The transmittance curves of the light conversion film M5 and the EPE high-transmittance film in this embodiment are shown.
[0090] Example 6 The synthesis method of a metal chelate LCA6 provided in this embodiment comprises the following steps: adding indium tribromide (100 mmol), 4,7-dimethyl-2,2-bipyridine (400 mmol), trioctylphosphine oxide (200 mmol) and dodecylpyridinium bromide (100 mmol) to a 1000 mL flask, and using 300 mL DMF as a solvent. Mixing is carried out in a ratio of M:L:A:B of 1:4:2:1. The formed mixture is then reacted at 60°C for 1 hour. Afterwards, it is cooled to room temperature, and the solvent is removed by evaporation to obtain LCA6, in which x=4, y=2, and z=1 in the chemical formula.
[0091] The structural formula of 4,7-dimethyl 2,2-bipyridine is as follows: .
[0092] LCA6 was directly added to the PVB polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 170°C. The light conversion film M6 was made using an upper casting machine, and its fluorescence quantum efficiency was 82%.
[0093] The UV aging box test shows that after continuous irradiation for 1000 hours under a 180-watt UV lamp, the attenuation index DN of the light conversion film M6 is 2%, showing good light stability. The light conversion film M6 is applied to the silicon crystalline photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 170°C. The compatibility index R600 of LCA6 and PVB in the light conversion film M6 is 0.998. Compared with the PVB high-transmittance film of the same thickness, the power of the silicon crystalline photovoltaic cell using the light conversion film M6 increased by 0.8%; compared with the high-cutoff film of the same thickness, the power increased by 1.9%.
[0094] Example 7 The synthesis method of a metal chelate LCA7 provided in this embodiment comprises the following steps: adding gadolinium trichloride (100 mmol), 1-thienyl-5-methyl-β-diketone (300 mmol), trimethylphosphine oxide (100 mmol) and tetradecyltrimethylammonium chloride (200 mmol) into a 1000 mL flask, and using 300 mL of methanol as a solvent. Then the formed mixture is reacted at 80°C for 3 hours. Afterwards, it is cooled to room temperature, and the solvent is removed by evaporation to obtain LCA7, in which x=3, y=1, and z=2 in the chemical formula.
[0095] The structural formula of 1-thienyl-5-methyl-β-diketone is as follows: .
[0096] LCA7 was directly added to the EPE polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 130°C, and an upper casting machine was used to make the light conversion film M7. The fluorescence quantum efficiency of the light conversion film M7 was 80%.
[0097] The UV aging box test shows that after continuous irradiation for 1000 hours under a 180-watt UV lamp, the attenuation index DN of the light conversion film M7 is 1.5%, showing good light stability. The light conversion film M7 is applied to the silicon crystalline photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 130°C. The compatibility index R600 of LCA7 and EPE in the light conversion film M7 is 0.996. Compared with the EPE high-transmittance film of the same thickness, the power of the silicon crystalline photovoltaic cell using the light conversion agent LCA7 increased by 0.5%; compared with the EPE high-cutoff film of the same thickness, the power increased by 1.5%.
[0098] Example 8 The synthesis method of a metal chelate LCA8 provided in this embodiment comprises the following steps: In a 1000 mL flask, europium tribromide (100 mmol), 3,8-dimethylphenanthroline (300 mmol), tributylphosphine oxide (200 mmol) were added, and 300 mL of acetonitrile was used as the solvent. The mixture was mixed in a ratio of M:L:A of 1:3:2. The resulting mixture was then reacted at 55°C for 4 hours. Afterwards, it was cooled to room temperature and the solvent was removed by evaporation to obtain LCA8, in which x=3, y=2, and z=0 in the chemical formula.
[0099] The structural formula of 3,8-dimethylphenanthroline is as follows: .
[0100] LCA8 was directly added to the EVA polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 120°C, and made into a light conversion film M8 using an upper casting machine. The fluorescence quantum efficiency of the light conversion film M8 was 68%.
[0101] The UV aging box test shows that after continuous irradiation for 1000 hours under a 150-watt UV lamp, the attenuation index DN of the light conversion film M8 is 1%, showing good light stability. The light conversion film M8 is applied to the silicon crystalline photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 120°C. The compatibility index R600 of LCA8 and EVA in the light conversion film M8 is 1.002. Compared with the EVA high-transmittance film of the same thickness, the power of the silicon crystalline photovoltaic cell using the light conversion agent LCA8 increased by 0.3%; compared with the EVA high-cutoff film of the same thickness, the power increased by 1%.
[0102] Example 9 The synthesis method of a metal chelate LCA9 provided in this embodiment comprises the following steps: Gadolinium trichloride (100 mmol), 4-methyl-7-cyano-8-hydroxyquinoline (400 mmol), trimethylphosphine oxide (100 mmol) and tetradecyltrimethylammonium bromide (200 mmol) were added to a 1000 mL flask, and 300 mL of ethanol was used as a solvent. The resulting mixture was then reacted at 100 °C for 2 hours. After cooling to room temperature, the solvent was removed by evaporation to obtain LCA9, whose chemical formula is x=4, y=1, and z=2.
[0103] The structural formula of 4-methyl 7-cyano 8-hydroxyquinoline is as follows: .
[0104] LCA9 was directly added to the PVB polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 140°C. The light conversion film M9 was made using an upper casting machine, and its fluorescence quantum efficiency was 80%.
[0105] The UV aging box test shows that after continuous irradiation for 1000 hours under a 180-watt UV lamp, the attenuation index DN of the light conversion film M9 is 2%, showing good light stability. The light conversion film M9 is applied to the silicon crystalline photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 140°C. The compatibility index R600 of LCA9 and PVB in the light conversion film M9 is 0.999. Compared with the PVB high-transmittance film of the same thickness, the power of the silicon crystalline photovoltaic cell using the light conversion film M9 increased by 0.5%; compared with the PVB high-cutoff film of the same thickness, the power increased by 1.8%.
[0106] Example 10 The synthesis method of a metal chelate LCA10 provided in this embodiment comprises the following steps: adding europium tribromide (100 mmol), 8-methyl 3-cyano 4-hydroxynaphthyridine (300 mmol), trioctylphosphine oxide (200 mmol) into a 1000 mL flask, and using 300 mL of dioxane as a solvent. Then the formed mixture is reacted at 70°C for 3 hours. Afterwards, it is cooled to room temperature, and the solvent is removed by evaporation to obtain LCA10, in which x=3, y=2, and z=0 in the chemical formula.
[0107] The structural formula of 8-methyl 3-cyano 4-hydroxynaphthyridine is as follows: .
[0108] LCA10 was directly added to the POE polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 130°C. The light conversion film M10 was made using an upper casting machine, and its fluorescent quantum efficiency was 67%.
[0109] The UV aging box test shows that after continuous irradiation for 1000 hours under a 150-watt UV lamp, the attenuation index DN of the light conversion film M10 is 2.5%, showing good light stability. The light conversion film M10 is applied to the silicon crystalline photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 130°C. The compatibility index R600 of LCA10 and POE in the light conversion film M10 is 1.002. Compared with the POE high-transmittance film of the same thickness, the power of the silicon crystalline photovoltaic cell using the light conversion film M10 increased by 0.4%; compared with the POE high-cutoff film of the same thickness, the power increased by 1.6%.
[0110] Embodiment 11 The synthesis method of a metal chelate LCA11 provided in this embodiment comprises the following steps: adding molybdenum trichloride (100 mmol), 5,6-dimethylphenanthroline (300 mmol), trimethylphosphine oxide (200 mmol) and dodecyltrimethylammonium bromide (200 mmol) into a 1000 mL flask, and using 300 mL THF as a solvent. Then the formed mixture is reacted at 90° C. for 3.5 hours. Afterwards, it is cooled to room temperature, and the solvent is removed by evaporation to obtain LCA11, in which x=3, y=2, and z=2 in the chemical formula.
[0111] The structural formula of 5,6-dimethylphenanthroline is as follows: .
[0112] LCA11 was directly added to the EPE polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 145°C. An upper casting machine was used to make the light conversion film M11, whose fluorescence quantum efficiency was 80%.
[0113] The UV aging box test shows that after continuous irradiation for 1000 hours under a 180-watt UV lamp, the attenuation index DN of the light conversion film M11 is 1%, showing excellent light stability. The light conversion film M11 is applied to the silicon crystalline photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 145°C. The compatibility index R600 of LCA11 and EPE in the light conversion film M11 is 0.997. Compared with the EPE high-transmittance film of the same thickness, the power of the silicon crystalline photovoltaic cell using the light conversion film M11 increased by 0.7%; compared with the EPE high-cutoff film of the same thickness, the power increased by 1.9%.
[0114] Example 12 The synthesis method of a metal chelate LCA12 provided in this embodiment comprises the following steps: adding 10.3 g of europium trichloride (100 mmol), 52.4 g of 4-methyl 8-hydroxyquinoline (400 mmol), 37.7 g of trimethylphosphine oxide (100 mmol) and 50 g of tetradecyltrimethylammonium chloride (200 mmol) into a 1000 mL flask, and using 300 mL of methanol as a solvent. The resulting mixture is then reacted at 55° C. for 4 hours. Afterwards, the mixture is cooled to room temperature, and the solvent is removed by evaporation to obtain LCA12, in which x=4, y=1, and z=2 in the chemical formula.
[0115] The structural formula of 4-methyl 8-hydroxyquinoline is as follows: .
[0116] LCA12 was directly added to the EPE polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 120°C. An upper casting machine was used to make the light conversion film M12, whose fluorescence quantum efficiency was 85%.
[0117] The UV aging box test shows that after continuous irradiation for 1000 hours under a 180-watt UV lamp, the attenuation index DN of the light conversion film M12 is 1%, showing excellent light stability. The light conversion film M12 is applied to the silicon crystalline photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 120°C. The compatibility index R600 of LCA12 and EPE in the light conversion film M12 is 1.003. Compared with the EPE high-transmittance film of the same thickness, the power of the silicon crystalline photovoltaic cell using the light conversion agent LCA12 increased by 0.9%; compared with the EPE high-cutoff film of the same thickness, the power increased by 1.7%.
[0118] Example 13 The synthesis method of a metal chelate LCA13 provided in this embodiment comprises the following steps: adding gadolinium trichloride (100 mmol), 4-methyl 7-cyano 8-hydroxyquinoline (300 mmol), tributylphosphine oxide (150 mmol) and dodecyltrimethylammonium bromide (50 mmol) into a 1000 mL flask, and using 300 mL acetonitrile as a solvent. Then the formed mixture is reacted at 80°C for 3 hours. Afterwards, it is cooled to room temperature, and the solvent is removed by evaporation to obtain LCA13, in which x=3, y=1.5, and z=0.5 in the chemical formula.
[0119] The structural formula of 4-methyl 7-cyano 8-hydroxyquinoline is as follows: .
[0120] LCA13 was directly added to the POE polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 135°C, and an upper casting machine was used to make the light conversion film M13. The fluorescence quantum efficiency of the light conversion film M13 was 73%.
[0121] The UV aging box test shows that after continuous irradiation for 1000 hours under a 180-watt UV lamp, the attenuation index DN of the light conversion film M13 is 2%, showing good light stability. The light conversion film M13 is applied to the silicon crystalline photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 135°C. The compatibility index R600 of LCA13 and POE in the light conversion film M13 is 0.998. Compared with the POE high-transmittance film of the same thickness, the power of the silicon crystalline photovoltaic cell using the light conversion agent LCA13 increased by 0.5%; compared with the high-cutoff film of the same thickness, the power increased by 1.6%.
[0122] Embodiment 14 The synthesis method of a metal chelate LCA14 provided in this embodiment comprises the following steps: europium tribromide (100 mmol), 3,8-dimethylphenanthroline (400 mmol), trioctylphosphine oxide (160 mmol) and tetradecyltrimethylammonium chloride (40 mmol) are added to a 1000 mL flask, and 300 mL DMF is used as a solvent. The resulting mixture is then reacted at 60° C. for 1 hour. Afterwards, the mixture is cooled to room temperature, and the solvent is removed by evaporation to obtain LCA14, in which x=4, y=1, and z=2 in the chemical formula.
[0123] The structural formula of 3,8-dimethylphenanthroline is as follows: .
[0124] LCA14 was directly added to the PVB polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 160°C. An upper casting machine was used to prepare the light conversion film M14, whose fluorescence quantum efficiency was 75%.
[0125] The UV aging box test shows that after continuous irradiation for 1000 hours under a 180-watt UV lamp, the attenuation index DN of the light conversion film M14 is 2%, showing good light stability. The light conversion film M14 is applied to the silicon crystalline photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 160°C. The compatibility index R600 of LCA14 and PVB in the light conversion film M14 is 1.002. Compared with the PVB high-transmittance film of the same thickness, the power of the silicon crystalline photovoltaic cell using the light conversion film M14 increased by 0.6%; compared with the PVB high-cutoff film of the same thickness, the power increased by 1.5%.
[0126] Embodiment 15 The synthesis method of a metal chelate LCA15 provided in this embodiment comprises the following steps: adding molybdenum trichloride (100 mmol), 1-pyrrolyl-5-isopropyl-β-diketone (300 mmol), trimethylphosphine oxide (120 mmol) and hexadecyltriethylammonium bromide (80 mmol) into a 1000 mL flask, and using 300 mL of ethanol as a solvent. Then the formed mixture is reacted at 70°C for 2 hours. After that, it is cooled to room temperature, and the solvent is removed by evaporation to obtain LCA15, in which x=3, y=1.2, and z=0.8 in the chemical formula.
[0127] The structural formula of 1-pyrrolyl-5-isopropyl-β-diketone is as follows: .
[0128] LCA15 was directly added to the EPE polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 145°C. The light conversion film M15 was made using an upper casting machine, and its fluorescence quantum efficiency was 80%.
[0129] The UV aging box test shows that after continuous irradiation for 1000 hours under a 150-watt UV lamp, the attenuation index DN of the light conversion film M15 is 1.5%, showing good light stability. The light conversion film M15 is applied to the silicon photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 145°C. The compatibility index R600 of LCA15 and EPE in the light conversion film M15 is 1.001. Compared with the EPE high-transmittance film of the same thickness, the power of the silicon photovoltaic cell using the light conversion film M15 has increased by 0.8%; compared with the EPE high-cutoff film of the same thickness, the power has increased by 1.7%.
[0130] Example 16 The synthesis method of a metal chelate LCA16 provided in this embodiment comprises the following steps: adding indium tribromide (100 mmol), 4,7-dimethyl-2,2-bipyridine (300 mmol), tributylphosphine oxide (200 mmol) and dodecylpyridinium bromide (100 mmol) into a 1000 mL flask, and using 300 mL of methanol as a solvent. The resulting mixture is then reacted at 55° C. for 3.5 hours. Afterwards, the mixture is cooled to room temperature, and the solvent is removed by evaporation to obtain LCA16, in which x=3, y=2, and z=1 in the chemical formula.
[0131] LCA16 was directly added to the POE polymer particles at a dosage of 1‰, stirred and blended for 1 hour, and then heated to 130°C. An upper casting machine was used to make the light conversion film M16, whose fluorescence quantum efficiency was 72%.
[0132] The UV aging box test shows that after continuous irradiation for 1000 hours under a 180-watt UV lamp, the attenuation index DN of the light conversion film M16 is 2%, showing good light stability. The light conversion film M16 is applied to the silicon crystalline photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 130°C. The compatibility index R600 of LCA16 and POE in the light conversion film M16 is 0.999. Compared with the POE high-transmittance film of the same thickness, the power of the silicon crystalline photovoltaic cell using the light conversion film M16 has increased by 0.4%; compared with the POE high-cutoff film of the same thickness, the power has increased by 1.4%.
[0133] Embodiment 17 The synthesis method of a metal chelate LCA17 provided in this embodiment comprises the following steps: adding gadolinium trichloride (100 mmol), 5,6-dimethylphenanthroline (300 mmol), trimethylphosphine oxide (100 mmol) and tetradecyltrimethylammonium bromide (100 mmol) into a 1000 mL flask, and using 300 mL THF as a solvent. Then the formed mixture is reacted at 80° C. for 2 hours. Afterwards, it is cooled to room temperature, and the solvent is removed by evaporation to obtain LCA17, in which x=3, y=1, and z=1 in the chemical formula.
[0134] The structural formula of 5,6-dimethylphenanthroline is as follows: .
[0135] LCA17 was directly added to the EVA polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 150°C. An upper casting machine was used to make the light conversion film M17, whose fluorescence quantum efficiency was 85%.
[0136] The UV aging box test shows that after continuous irradiation for 1000 hours under a 150-watt UV lamp, the attenuation index DN of the light conversion film M17 is 2.5%, showing good light stability. The light conversion film M17 is applied to the silicon crystalline photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 150°C. The compatibility index R600 of LCA17 and EVA in the light conversion film M17 is 1.001. Compared with the EVA high-transmittance film of the same thickness, the power of the silicon crystalline photovoltaic cell using the light conversion film M17 has increased by 0.5%; compared with the EVA high-cutoff film of the same thickness, the power has increased by 1.5%.
[0137] Embodiment 18 The synthesis method of a metal chelate LCA18 provided in this embodiment comprises the following steps: adding aluminum chloride (100 mmol), 8-methyl 3-cyano 4-hydroxynaphthyridine (300 mmol), tri-n-butylphosphine oxide (200 mmol) and dodecylpyridinium bromide (200 mmol) into a 1000 mL flask, and using 300 mL of isopropanol as a solvent. Then the formed mixture is reacted at 55° C. for 4 hours. Afterwards, it is cooled to room temperature, and the solvent is removed by evaporation to obtain LCA18, in which x=3, y=2, and z=2 in the chemical formula.
[0138] The structural formula of 8-methyl 3-cyano 4-hydroxynaphthyridine is as follows: .
[0139] LCA18 was directly added to the PVB polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 120°C. The light conversion film M18 was made using an upper casting machine, and its fluorescence quantum efficiency was 76%.
[0140] The UV aging box test shows that after continuous irradiation for 1000 hours under a 180-watt UV lamp, the attenuation index DN of the light conversion film M18 is 1%, showing excellent light stability. The light conversion film M18 is applied to the silicon crystalline photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 120°C. The compatibility index R600 of LCA18 and PVB in the light conversion film M18 is 0.998. Compared with the PVB high-transmittance film of the same thickness, the power of the silicon crystalline photovoltaic cell using the light conversion agent LCA18 has increased by 0.7%; compared with the PVB high-cutoff film of the same thickness, the power has increased by 1.8%.
[0141] Embodiment 19 The synthesis method of a metal chelate LCA19 provided in this embodiment comprises the following steps: adding europium tribromide (100 mmol), 1-thienyl-5-methyl-β-diketone (300 mmol), trimethylphosphine oxide (200 mmol) and tetradecyltrimethylammonium chloride (100 mmol) into a 1000 mL flask, and using 300 mL of dioxane as a solvent. The resulting mixture is then reacted at 65° C. for 3 hours. Afterwards, the mixture is cooled to room temperature, and the solvent is removed by evaporation to obtain LCA19, in which x=3, y=2, and z=1 in the chemical formula.
[0142] The structural formula of 1-thienyl-5-methyl-β-diketone is as follows: .
[0143] LCA19 was directly added to the EPE polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 140°C. The light conversion film M19 was made using an upper casting machine, and its fluorescence quantum efficiency was 75%.
[0144] The UV aging box test shows that after continuous irradiation for 1000 hours under a 180-watt UV lamp, the attenuation index DN of the light conversion film M19 is 2%, showing good light stability. The light conversion film M19 is applied to the silicon crystalline photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 140°C. The compatibility index R600 of LCA19 and EPE in the light conversion film M19 is 1.001. Compared with the EPE high-transmittance film of the same thickness, the power of the silicon crystalline photovoltaic cell using the light conversion film M19 has increased by 0.6%; compared with the EPE high-cutoff film of the same thickness, the power has increased by 1.9%.
[0145] Embodiment 20 The synthesis method of a metal chelate LCA20 provided in this embodiment comprises the following steps: adding aluminum chloride (100 mmol), 4-methyl 8-hydroxyquinoline (400 mmol), trioctylphosphine oxide (200 mmol) and hexadecyltriethylammonium bromide (200 mmol) into a 1000 mL flask, and using 300 mL of methanol as a solvent. Then the formed mixture is reacted at 50° C. for 1 hour. Afterwards, it is cooled to room temperature, and the solvent is removed by evaporation to obtain LCA20, in which x=4, y=2, and z=2 in the chemical formula.
[0146] The structural formula of 4-methyl 8-hydroxyquinoline is as follows: .
[0147] LCA20 was directly added to the POE polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 110°C. The light conversion film M20 was made using an upper casting machine, and its fluorescence quantum efficiency was 88%.
[0148] The UV aging box test shows that after continuous irradiation for 1000 hours under a 150-watt UV lamp, the attenuation index DN of the light conversion film M20 is 1.5%, showing good light stability. The light conversion film M20 is applied to the silicon photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 110°C. The compatibility index R600 of LCA20 and POE in the light conversion film M20 is 1.003. Compared with the POE high-transmittance film of the same thickness, the power of the silicon photovoltaic cell using the light conversion film M20 has increased by 0.3%; compared with the POE high-cutoff film of the same thickness, the power has increased by 1%.
[0149] Embodiment 21 The synthesis method of a metal chelate LCA21 provided in this embodiment comprises the following steps: adding molybdenum trichloride (100 mmol), 3,8-dimethylphenanthroline (300 mmol), trimethylphosphine oxide (150 mmol) and dodecyltrimethylammonium bromide (150 mmol) into a 1000 mL flask, and using 300 mL acetonitrile as a solvent. The resulting mixture is then reacted at 58°C for 3 hours. Afterwards, the mixture is cooled to room temperature, and the solvent is removed by evaporation to obtain LCA21, in which the chemical formula has x=3, y=1.5, and z=1.5.
[0150] The structural formula of 3,8-dimethylphenanthroline is as follows: .
[0151] LCA21 was directly added to the EVA polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 120°C. An upper casting machine was used to prepare the light conversion film M21, whose fluorescence quantum efficiency was 72%.
[0152] The UV aging box test shows that after continuous irradiation for 1000 hours under a 180-watt UV lamp, the attenuation index DN of the light conversion film M21 is 2%, showing good light stability. The light conversion film M21 is applied to the silicon crystalline photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 120°C. The compatibility index R600 of LCA21 and EVA in the light conversion film M21 is 0.999. Compared with the EVA high-transmittance film of the same thickness, the power of the silicon crystalline photovoltaic cell using the light conversion film M21 has increased by 0.5%; compared with the EVA high-cutoff film of the same thickness, the power has increased by 1.6%.
[0153] Embodiment 22 The synthesis method of a metal chelate LCA22 provided in this embodiment comprises the following steps: adding aluminum chloride (100 mmol), 2,2-bipyridine (300 mmol), tributylphosphine oxide (200 mmol) and tetradecyltrimethylammonium bromide (1 mmol) into a 1000 mL flask, and using 300 mL DMF as a solvent. Then the formed mixture is reacted at 70°C for 2.5 hours. After that, it is cooled to room temperature, and the solvent is removed by evaporation to obtain LCA22, in which x=3, y=2, and z=1 in the chemical formula.
[0154] LCA22 was directly added to the PVB polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 135°C. An upper casting machine was used to prepare the light conversion film M22, whose fluorescence quantum efficiency was 78%.
[0155] The UV aging box test shows that after continuous irradiation for 1000 hours under a 150-watt UV lamp, the attenuation index DN of the light conversion film M22 is 1.2%, showing excellent light stability. The light conversion film M22 is applied to the silicon crystalline photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 135°C. The compatibility index R600 of LCA22 and PVB in the light conversion film M22 is 1.003. Compared with the PVB high-transmittance film of the same thickness, the power of the silicon crystalline photovoltaic cell using the light conversion film M22 has increased by 0.9%; compared with the PVB high-cutoff film of the same thickness, the power has increased by 1.8%.
[0156] Embodiment 23 The synthesis method of a metal chelate LCA23 provided in this embodiment comprises the following steps: adding europium tribromide (100 mmol), 4-methyl 7-cyano 8-hydroxyquinoline (400 mmol), trioctylphosphine oxide (120 mmol) and dodecylpyridinium bromide (80 mmol) into a 1000 mL flask, and using 300 mL THF as a solvent. Then the formed mixture is reacted at 60° C. for 3 hours. Afterwards, it is cooled to room temperature, and the solvent is removed by evaporation to obtain LCA23, in which x=4, y=1.2, and z=0.8 in the chemical formula.
[0157] The structural formula of 4-methyl 7-cyano 8-hydroxyquinoline is as follows: .
[0158] LCA23 was directly added to the EPE polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 145°C. An upper casting machine was used to prepare the light conversion film M23, whose fluorescence quantum efficiency was 77%.
[0159] The UV aging box test shows that after continuous irradiation for 1000 hours under a 180-watt UV lamp, the attenuation index DN of the light conversion film M23 is 1.5%, showing good light stability. The light conversion film M23 is applied to the silicon crystalline photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 145°C. The compatibility index R600 of LCA23 and EPE in the light conversion film M23 is 0.997. Compared with the EPE high-transmittance film of the same thickness, the power of the silicon crystalline photovoltaic cell using the light conversion film M23 has increased by 0.7%; compared with the EPE high-cutoff film of the same thickness, the power has increased by 1.7%.
[0160] Embodiment 24 The synthesis method of a metal chelate LCA24 provided in this embodiment comprises the following steps: adding molybdenum trichloride (100 mmol), 8-methyl 3-cyano 4-hydroxynaphthyridine (300 mmol), trimethylphosphine oxide (200 mmol) and tetradecyltrimethylammonium chloride (200 mmol) into a 1000 mL flask, and using 300 mL of ethanol as a solvent. Then the formed mixture is reacted at 80°C for 2 hours. Afterwards, it is cooled to room temperature, and the solvent is removed by evaporation to obtain LCA24, in which x=3, y=2, and z=2 in the chemical formula.
[0161] The structural formula of 8-methyl 3-cyano 4-hydroxynaphthyridine is as follows: .
[0162] LCA24 was directly added to the POE polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 130°C. An upper casting machine was used to make the light conversion film M24, whose fluorescence quantum efficiency was 88%.
[0163] The UV aging box test shows that after continuous irradiation for 1000 hours under a 180-watt UV lamp, the attenuation index DN of the light conversion film M24 is 2%, showing good light stability. The light conversion film M24 is applied to the silicon crystalline photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 130°C. The compatibility index R600 of LCA24 and POE in the light conversion film M24 is 1.002. Compared with the POE high-transmittance film of the same thickness, the power of the silicon crystalline photovoltaic cell using the light conversion agent LCA24 has increased by 0.4%; compared with the POE high-cutoff film of the same thickness, the power has increased by 1.3%.
[0164] Embodiment 25 The synthesis method of a metal chelate LCA25 provided in this embodiment comprises the following steps: adding indium tribromide (100 mmol), 5,6-dimethylphenanthroline (400 mmol), tributylphosphine oxide (200 mmol) and hexadecyltriethylammonium bromide (100 mmol) to a 1000 mL flask, and using 300 mL DMF as a solvent. The resulting mixture is then reacted at 65° C. for 3.5 hours. Afterwards, the mixture is cooled to room temperature, and the solvent is removed by evaporation to obtain LCA25, in which x=4, y=2, and z=1 in the chemical formula.
[0165] The structural formula of 5,6-dimethylphenanthroline is as follows: .
[0166] LCA25 was directly added to the EPE polymer particles at an addition amount of 1‰, stirred and blended for 1 hour, and then heated to 155°C. The light conversion film M25 was made using an upper casting machine, and its fluorescence quantum efficiency was 70%.
[0167] The UV aging box test shows that after continuous irradiation for 1000 hours under a 150-watt UV lamp, the attenuation index DN of the light conversion film M25 is 1%, showing excellent light stability. The light conversion film M25 is applied to the silicon crystalline photovoltaic cell using a vacuum laminator, and the lamination temperature is controlled at 155°C. The compatibility index R600 of LCA25 and EPE in the light conversion film M25 is 0.999. Compared with the EPE high-transmittance film of the same thickness, the power of the silicon crystalline photovoltaic cell using the light conversion film M25 has increased by 0.6%; compared with the EPE high-cutoff film of the same thickness, the power has increased by 1.5%.
[0168] Table 1 Performance test results of the light conversion films of metal chelates based on the examples and comparative examples of the present application
[0169] Note: The power increase rate I of silicon photovoltaic cells in Table 1 is the increase in the power of silicon photovoltaic cells using a metal chelate-based light conversion film compared to the power of silicon photovoltaic cells using a high-transmittance film in each embodiment (or comparative example); the power increase rate II of silicon photovoltaic cells is the increase in the power of silicon photovoltaic cells using a metal chelate-based light conversion film compared to the power of silicon photovoltaic cells using a high-cutoff film in each embodiment (or comparative example). In addition, the metal chelate-based light conversion film, the high-transmittance film and the high-cutoff film in each embodiment are formed based on the same film-forming polymer and have the same thickness, and the content of metal chelate in the metal chelate-based light conversion film in each embodiment is similar to the content of ultraviolet absorbing material (light stabilizer 744) in the high-cutoff film.
[0170] Application Example 1 The metal chelate LCA3 prepared in Example 3 was dissolved in anhydrous ethanol to form a solution with a concentration of about 5 wt%. The solution was then used to draw a squirrel pattern on filter paper. Figure 6 The squirrel pattern is invisible to the naked eye under visible light, but can be clearly seen under ultraviolet light. This phenomenon shows that LCA1 has application value in the field of anti-counterfeiting.
[0171] Application Example 2 The metal chelate LCA3 prepared in Example 3 was directly added to PC (polycarbonate) at an addition amount of 1‰, and then prepared into a transparent profile by injection molding or the like. Figure 7 As shown, the transparent profile is colorless and transparent under natural light, but presents bright colors under ultraviolet light. Therefore, the transparent profile can be used to prepare decorative lamps, which have no thermal effect when used and are low in cost. In addition, by changing the amount of LCA3 added, the prepared transparent profile can also present different colors under ultraviolet light.
[0172] Although the present application has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions, and / or additions may be made and that elements of the described embodiments may be substituted with substantial equivalents without departing from the spirit and scope of the present application. In addition, many modifications may be made to adapt a particular situation or material to the teachings of the present application without departing from the scope of the present application. Therefore, it is not intended herein to limit the present application to the disclosed specific embodiments for carrying out the present application, but rather it is intended that the present application will include all embodiments within the scope of the appended claims.
Claims
1. A metal chelate, characterized in that: The chemical formula of the metal chelate is ML x A y B z , wherein M is at least selected from the group consisting of main metal ions, transition metal ions or rare earth metal ions, L is selected from a rigid chelating agent having two or more electron-donating functional groups, A is selected from a phosphine oxide compound having 1 to 3 aliphatic substituents or aromatic substituents, B is selected from an alkyl cationic surfactant, x=2 to 4, (y+z)=0 to 4, x is an integer, y and z are both greater than or equal to 0, and y and z are not 0 at the same time.
2. The metal chelate according to claim 1, characterized in that: M is selected from trivalent metal ions; and / or, L comprises a hydroxyquinoline derivative, a hydroxynaphthyridine derivative, a b-diketone derivative or an o-phenanthroline derivative; and / or, the carbon number of each aliphatic substituent or aromatic substituent in A is 1 to 20; And / or, the hydrophilic group in the alkyl cationic surfactant includes an ammonium cation, and the hydrophobic group includes an alkyl group with a carbon number of 1 to 20.
3. The metal chelate according to claim 2, characterized in that: M is at least selected from Al 3+ , Ga 3+ 、In 3+ 、Mo 3+ 、Eu 3+ Sc 3+ , Gd 3+ or Y 3+ ; And / or, L is at least one or more combinations selected from the following compounds: ; Among them, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 are independently selected from hydrogen or an aliphatic substituent or an aromatic substituent having 1 to 20 carbon atoms; and / or, the aliphatic substituent in A includes a saturated alkyl group or a saturated alkoxy group, and the aromatic substituent includes an aromatic hydrocarbon group; And / or, the hydrophilic group in the alkyl cationic surfactant includes trimethylammonium bromide ion, trimethylammonium chloride ion, triethylammonium bromide ion, triethylammonium chloride ion, pyridinium bromide ion or pyridinium chloride ion, and the hydrophobic group includes dodecyl, tetradecyl or hexadecyl.
4. The metal chelate according to claim 3, characterized in that: The saturated alkyl group includes methyl, ethyl, propyl, butyl, hexyl or octyl, the saturated alkoxy group includes methoxy, ethoxy, propoxy, butoxy, hexyl or octyl, and the aromatic hydrocarbon group includes phenyl, benzyl, thienyl or pyrrolyl.
5. A method for preparing a metal chelate, characterized in that: include: A mixture containing MX3, L, A, B and anhydrous polar solvent is reacted at 50-110°C to prepare a light conversion material ML. x A y B z ; Wherein, M is a trivalent metal ion and is at least selected from a family metal ion, a transition metal ion or a rare earth metal ion, X is selected from a halogen ion, L is selected from a rigid chelating agent having two or more functional groups, A is selected from a phosphine oxide compound containing 1 to 3 aliphatic substituents or aromatic substituents, B is selected from an alkyl cationic surfactant, x=2 to 4, (y+z)=0 to 4, x is an integer, y and z are both greater than or equal to 0, and y and z are not 0 at the same time.
6. The preparation method according to claim 5, characterized in that: Specifically include: The mixture is reacted at 50-110° C. for 1-10 hours, then cooled to room temperature, and the solvent is removed to obtain the metal chelate; and / or, X is at least selected from F - , Cl - or Br - ; and / or, the mass ratio of MX3, L, A and B is 1:1~4:0~4:0~4; And / or, the anhydrous polar solvent includes one or more combinations of methanol, ethanol, isopropanol, acetonitrile, DMF, THF, and dioxane.
7. Use of the metal chelate according to any one of claims 1 to 4 in preparing a photoconversion material, wherein the photoconversion material is capable of converting absorbed light of a first wavelength into light of a second wavelength, wherein the second wavelength is greater than the first wavelength.
8. The use according to claim 7, characterized in that: The first wavelength of light includes ultraviolet light.
9. A down-conversion luminescent material, characterized in that: The invention comprises the metal chelate compound according to any one of claims 1 to 4.
10. Use of the metal chelate compound according to any one of claims 1 to 4 or the down-conversion luminescent material according to claim 9 in the preparation of a photovoltaic device, an anti-counterfeiting structure or a luminescent structure.
11. An optical structure comprising a base component and a light conversion agent dispersed in the base component, characterized in that: The photoconversion agent comprises the metal chelate compound according to any one of claims 1 to 4 or the down-conversion luminescent material according to claim 9.
12. The optical structure according to claim 11, characterized in that: The optical structure comprises 0.2wt‰~5wt‰ light conversion agent; And / or, the base component comprises a polymer, and the polymer comprises a combination of one or more of EVA, PVB, POE or EPE; And / or, the optical structure is in the form of a film; And / or, the light transmittance of the optical structure is above 80%.
13. A method for preparing an optical structure, characterized in that: include: At least a light conversion agent is mixed with a polymer, and then the resulting mixture is heated and melted at a set temperature to form an optical structure; Wherein, the photoconverter comprises the metal chelate according to any one of claims 1 to 4, and the mass ratio of the metal chelate to the polymer is 0.2‰ to 5‰, and the set temperature is above the glass transition temperature of the polymer.
14. The preparation method according to claim 13, characterized in that: Specifically include: Mixing the photoconverter or the solution of the photoconverter with polymer particles to obtain the mixture; And / or, the mixture is heated and melted to form a film, thereby obtaining the optical structure.
15. A photovoltaic device, comprising a photovoltaic cell and a packaging structure connected to the photovoltaic cell, characterized in that: The packaging structure comprises the optical structure according to any one of claims 11-12.
16. The photovoltaic device according to claim 15, characterized in that: The photovoltaic cell includes a silicon solar cell, a perovskite photovoltaic cell, an organic photovoltaic cell, a copper indium selenide photovoltaic cell, a gallium arsenide photovoltaic cell or a cadmium telluride photovoltaic cell.
17. An anti-counterfeiting structure, comprising a substrate and an anti-counterfeiting material layer distributed on the surface of the substrate, characterized in that: The anti-counterfeiting material layer comprises the metal chelate compound according to any one of claims 1 to 4 or the down-conversion luminescent material according to claim 9.
18. A light emitting device, comprising a light source and a light conversion structure cooperating with the light source, characterized in that: The light conversion structure comprises the metal chelate compound according to any one of claims 1 to 4, the down-conversion luminescent material according to claim 9, or the optical structure according to any one of claims 11 to 12.
Citation Information
Patent Citations
Ionic rare-earth complex luminescent material and preparation method and application therefor
CN104844594A
High-thermal-stability and migration-resistant organic light-emitting material as well as preparation method and application thereof
CN111057078A
Production and preparation method of 4-hydroxy-1, 5-naphthyridine europium complex
CN114591354A
Preparation method of ionic 4-hydroxy-1, 5-naphthyridine europium complex
CN117551096A
